Primary Care Perspectives on Surgical Interventions for Obstructive Sleep Apnea - Ogbeide, Angel; Munk, Devan; Clemow, Justin; Ogbeide, Stacy (Translation: The University of Toledo Journal of Medical Sciences, 2025)
The main source of diagnosis and treatment of OSA is through primary care, namely family medicine. Since the family medicine physician is typically the main source of medical knowledge for most patients, the knowledge base of family medicine residents on surgical treatment options to address OSA should be considered of paramount importance. The lack of knowledge regarding surgical treatment options limits patient care and favorable treatment outcomes. The purpose of this project is to assess the knowledge base of family medicine residents in ACGME accredited programs in the surgical treatment options available for management of Obstructive Sleep Apnea to further provide training institutions information on modifying resident education in the fields related to sleep medicine. This project was conducted by providing a 20-question survey to family medicine residents at ACGME accredited programs. A total of 28 responses were received from family medicine residents throughout the United States. Residents generally feel comfortable in screening patients for OSA. However, there is a distinct knowledge gap regarding the surgical treatment options available to patients. More integrated educational opportunities through grand rounds, collaborative rotations, or even CME lectures can address these knowledge gaps and thus improve patient care.